Hubungan antara Neutropenia dan Mortalitas pada Neonatus dengan Sepsis, dengan MengendalikanPengaruh Umur Gestasi dan Berat Badan lahir - Rokhayati, Evi (Jurnal Kedokteran Indonesia, 2011)
Background: Sepsis in neonates (newborns) remains a major cause of public health concern. Sepsismay cause neutropenia due to hematological system dysfunction, which suggests poor prognosis.Decreased neutrophil function will increase mortality in neonates. In addition, the health care costimplication of residual symptoms in children who survive is quite high.This study aimed to estimatethe association between neutropenia and mortality in neonates with sepsis.Methods: A prospective cohort study was conducted at Dr. Moewardi Hospital, Surakarta. A sample of85 neonates was selected by consecutive sampling, i.e. all of the newborns aged <1 month at thePedicatric Intensive Care Unit at this hospital during April 2011 to July 2011 period were taken as thestudy subjects. The dependent variable was time to mortality. The independent variabel wasneutropenia. The confounding factors were gestational age (prematurity) and low birth weight. Theassociation between neotropenia and time to mortality while controlling for gestational age and birthweight was analyzed by Cox-regression model on SPSS 17.0Results: The sample consisted of 54 (63.5%) male and 31 (36.5%) female newborns. There were 40(47.10%) newborns with gestational age <37 weeks, and 45 (52.90%) with weight <2500g. As many as44 (51.80%) newborns experienced neutropenia while 41 (48.20%) did not experience neutropenia.The death toll of these newborns was 27 (31.80%). Cox regression analysis showed a weak associationbetween neotropenia and mortality, and it was not statistically signficant (Hazard Ratio = 1.28; 95% CI0.55 to 2.94; p=0.568). This estimate has controlled for the effects of gestational age and birth weight.Prematurity showed strong association with the risk of mortality in neonates with sepsis (HR = 3.12;95% CI 1.07 to 9.68; p=0.037).Conclusion: Neutropenia and in addition low birth weight show weak and unreliable predictors formortaity in neonates with sepsis. Prematurity shows a strong and reliable predictor for mortality inneonates with sepsis.Keywords: sepsis, neutropenia, mortality, neonates.